MODEL PEMBELAJARAN TWO STAY TWO STRAY DAN HASIL BELAJAR KOGNITIF - Fitrianti Fitrianti; Supardi U.S. (Social Sciences, Humanities and Education Journal (SHE Journal), 2021)
This study aims to analyze the effect of the Two Stay Two Stray learning model on cognitive learning outcomes for the Diversity of Living Things and Their Conservation Efforts. The research was conducted by using a quasi-experimental method on seventh grade students of SMPN in Serang Regency, Banten Province. The research data were analyzed using statistics of descriptive and t-test inferential. The results showed that the cognitive learning outcomes who were taught using conventional learning models had an average score of 71.7; while for students who used the Two Stay Two Stray learning model obtained an average score of 78.8. The results of inferential analysis obtained t-count = 3.694 higher than t-table = 1.729 so that it can be concluded that there is a significant effect of the Two Stay Two Stray learning model on the cognitive learning outcomes of the Diversity of Living Things and Their Conservation Efforts. In order to improve student cognitive learning outcomes, teachers should use the Two Stay Two Stray model in the learning process in the classroom.